Peningkatan Kompetensi Guru dalam Implementasi Kurikulum Merdeka (IKM) melalui in House Training (IHT) di SDIT Darul Ulum - Virgiyanti, Dita; Dewi, Indria Kusuma; Zuliani, Rizki (Lembaga Yasin AlSys, 2023)
The Merdeka Curriculum was designed as an effort by the Ministry of Education and Culture to overcome the learning crisis that we have been facing for a long time, and which is getting worse due to the co-19 pandemic. This crisis is marked by the low learning outcomes of students, even in basic matters such as reading literacy. One of the determining factors for the successful implementation of teaching and learning activities is the teacher. So a teacher must understand the curriculum comprehensively from the theoretical concept to its implementation in the classroom. There are various types of training that are commonly used in In House Training, which is a training program that is held at the training participant's place or at school by optimizing the potentials that exist in schools. House Training (IHT) at SDIT Darul Ulum and analyzing the results. Through this CAR, researchers are trying to improve the ability of teachers in the Implementation of the Independent Curriculum (IKM) through IHT at SDIT Darul Ulum. In this study IHT was carried out in three steps, namely: (1) Planning, (2) Implementation and Observation, 3) Evaluation of IHT. IHT activities can improve teachers' abilities in implementing the Independent Curriculum (IKM) through IHT at SDIT Darul Ulum with grades in cycle 1. Researchers also provide recommendations to other researchers to develop innovative learning in IKM according to learning process standards.